Serum levels of inflammatory markers CRP, ESR and albumin in relation to survival for patients with hepatocellular carcinoma. Issue 2 (12th December 2020) - Akkiz, Hikmet; Carr, Brian I.; Bag, Harika G.; Karaoğullarından, Ümit; Yalçın, Kendal; Ekin, Nazim; Özakyol, Ayşegül; Altıntaş, Engin; Balaban, Hatice Y.; Şimşek, Halis; Uyanıkoğlu, Ahmet; Balkan, Ayhan; et al.
Abstract: Introduction: Hepatocellular carcinoma is associated with several chronic inflammatory conditions. It is increasingly understood that the inflammation may be part of the carcinogenic process and prognostically important. Objective: To evaluate the serum levels of three inflammation markers in relation to survival in HCC patients. Methods: We retrospectively examined the serum levels of CRP, albumin and ESR, both singly and in combination, in relation to patient survival. Results: Survival worsened with increase in CRP or ESR or decrease in albumin levels. Combinations of CRP plus albumin or CRP plus ESR were associated with an even greater range of survival (3‐fold), together with significant differences in maximum tumor diameter (PVT) and percent of patients with portal vein thrombosis (PVT). The triplet of CRP plus albumin plus ESR was associated with a sevenfold difference in survival, comparing low vs high parameter levels. These significant differences were found in patients with small or large tumors. Conclusions: Combinations of CRP with albumin or ESR or all three parameters together significantly related to differences in survival and to differences in MTD and percent PVT, in patients with both small and large size HCCs.